Middle income access to justice - Trebilcock, M. J.; Sossin, Lorne, 1964-; Duggan, A. J. (University of Toronto Press, 2012)
Middle Income Access to Justice presents a variety of innovative solutions, from dispute resolution process reforms to the development of non-lawyer forms of assistance and new methods for funding legal expenses.